Binding of the peptide deformylase on the ribosome surface modulates the exit tunnel interior - McGrath, Hugo; Černeková, Michaela; Kolář, Michal H (Biophysical journal, 2022)
Proteosynthesis on ribosomes is regulated at many levels. Conformational changes of the ribosome, possibly induced by external factors, may transfer over large distances and contribute to the regulation. The molecular principles of this long-distance allostery within the ribosome remain poorly understood. Here, we use structural analysis and atomistic molecular dynamics simulations to investigate peptide deformylase (PDF), an enzyme that binds to the ribosome surface near the ribosomal protein uL22 during translation and chemically modifies the emerging nascent peptide. Our simulations of the entire ribosome-PDF complex reveal that the PDF undergoes a swaying motion on the ribosome surface at the submicrosecond timescale. We show that the PDF affects the conformational dynamics of parts of the ribosome over distances of more than 5 nm. Using a supervised-learning algorithm, we demonstrate that the exit tunnel is influenced by the presence or absence of PDF. Our findings suggest a possible effect of the PDF on the nascent peptide translocation through the ribosome exit tunnel.
Keywords: Ribosomes; ribozomy